Synthesis, characterization, and molecular modeling studies of novel polyurethanes based on 2,2 '-[ethane-1,2-diylbis(nitrilomethylylidene)]diphenol and 2,2 '-[hexane-1,6-diylbis(nitrilomethylylidene)]diphenol hard segments - Raghu, A. V.; Gadaginamath, G. S.; Jawalkar, S. S.; Halligudi, Shivaraj B.; Aminabhavi, T. A. (Journal of Polymer Science Part A-Polymer Chemistry, 2006)
Novel polyurethanes (PUS) based on 2,2 `-[ethane-1,2-diylbis(nitrilomethylylidene)]diphenol and 2,2 `-[hexane-1,6-diylbis(nitrilomethylylidene)]diphenol as hard segments containing four aromatic diisocyanates (4,4 `-diphenylmethane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate) have been prepared. Fourier transform infrared, UV spectrophotometry, fluorescence spectroscopy, H-1 NMR and C-13 NMR spectroscopy, thermogravimetric analysis, and differential thermal analysis have been used to determine the structural characterization and thermal properties of the segmented PUS. All the PUS contain domains of both semicrystalline and amorphous structures, as indicated by X-ray diffraction. The acoustic properties have been calculated with the group contribution method. Molecular dynamics simulations have been performed on all the PUS to estimate the cohesive energy density and solubility parameter values, which compare well with the values calculated with the group contribution method. Furthermore, the simulation protocols have been applied to the PUS to produce X-ray diffraction plots to determine the phase morphology of the PUS. The surface properties of the PUS have been estimated from the simulation protocols. (c) 2006 Wiley Periodicals, Inc.
Keywords: amorphous; hard segments; molecular dynamics; Morphology; polyurethanes; Schiff base containing polymers; Thermal properties

Synthesis and characterization of novel schiff base polyurethanes - Raghu, A. V.; Gadaginamath, G. S.; Jeong, Han Mo; Mathew, Nevin T.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2009)
Eight different types of novel polyurethanes (PUs) were synthesized through the polyaddition reaction of 4,4'-(ethane-1,2-diylidenedinitrilo)diphenol and 4,4'(pentane-1,5-diylidenedinitrilo)diphenol with four different diisocyanates: 4,4'-diphenylmethane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate. The resulting PUs were soluble in polar, aprotic solvents. Structures of the diols and PUs were established with Ultraviolet-visible, fluorescence, Fourier transform infrared (FTIR), (1)H-NMR, and (13)C-NMR spectroscopy data. FTIR and NMR spectral data indicated the disappearance of both hydroxyl and isocyanate groups in the PUs. The thermal properties were investigated with thermogravimetry and differential scanning calorimetry. The weight losses, glass transitions, onset temperatures, and crystalline melting temperatures were measured. All the PUs exhibited semicrystalline and amorphous morphologies, as indicated by X-ray diffraction. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 113: 2747-2754, 2009
Keywords: amorphous; Morphology; polyurethanes; synthesis; Thermal properties

Elucidating the influence of structure and Ag+ -Na+ ion-exchange on crack-resistance and ionic conductivity of Na3Al1.8Si1.65 P-1.8 O-12 glass electrolyte - Keshri, Shweta R.; Mandal, Indrajeet; Ganisetti, Sudheer; Kasimuthumaniyan, S.; Kumar, Rajesh; Gaddam, Anuraag; Shelke, Ankita; Ajithkumar, Thalasseril G.; Gosvami, Nitya Nand; Krishnan, N. M. Anoop; Allu, Amarnath R. (Acta Materialia, 2022)
Glasses are emerging as promising and efficient solid electrolytes for all-solid-state sodium-ion batteries. However, they still suffer from poor ionic conductivity and crack-resistance, which need to be improved for better battery performance, reliability, and service life. The current study shows a significant enhancement in crack resistance (from 11.3 N to 32.9 N) for Na3Al (1.8) Si-1.65 P1.8O12 glass (Ag-0 glass) upon Na+ -Ag+ ion-exchange (IE) due to compressive stresses generated in the glass surface while the ionic conductivity values (similar to 10(-5) S/cm at 473 K) were retained. In this study, magic angle spinning-nuclear magnetic resonance (MAS-NMR), molecular dynamics (MD) simulations, Vickers micro hardness, and impedance spectroscopic techniques were used to evaluate the intermediate-range structure, atomic structure, crack resistance and conductivity of the glass. MAS-NMR and MD simulations confirm the presence of Si-OAl-O-P groups in the glass, thus enabling formation of Na percolated channel regions. AC-conductivity analysis for Ag-0 and ion-exchanged Ag-0 glass suggests that the mobility of Na+ ion increases with increasing temperature. It is observed that the measured mean square displacement (root < R-2(t(p))>) for sodium cations using AC-conductivity isotherms is nearly constant up to 448 K and then increases with increasing temperature up to 523 K. From the impedance spectra for ion-exchanged Ag-0 glass, it is identified that the increase in root < R-2 (t(nu))> and thereby, the mobility of sodium-ions for Ag-0 glass is due to the structural variations in the Ag-0 glass with increasing the temperature. Overall, the mechanisms presented in this article helps in formulating better glass based electrolyte materials for room temperature or high temperature sodium-ion batteries. (C) 2022 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: amorphous; Ion-exchange; Ionic-conductivity; MD simulations; Mechanical property

Bifunctional nanoelectrocatalyst: semi-amorphous cobalt tungstate-based nanocomposites surpassing amorphous and crystalline counterparts - Dev, Sahil; Nagappan, Sreenivasan; Kundu, Subrata; Mukherjee, Shatabdi Porel (ACS Applied Materials & Interfaces, 2025)
Electrocatalytic water splitting to hydrogen and oxygen is considered to be one of the significant routes for future renewable energy conversion. Therefore, the development of unique, efficient, and cost-effective bifunctional electrocatalysts, which can perform both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), is critical for the accessible utilization of renewable energy. The increasing overall efficiency of the water-splitting reaction is pivotal for sustainable energy conversion and hydrogen production. Herein, we present a facile solution-based synthesis route to control the crystallinity of the cobalt tungstate (CoWO4) nanomaterials to amorphous, semiamorphous, and crystalline phases and further exploit these nanomaterials as bifunctional electrocatalysts for the HER, OER, and overall electrochemical water splitting reaction. Notably, the semiamorphous cobalt tungstate nanomaterials show a remarkable surface area of approximately 150 m(2)/g, the highest reported for CoWO4-based materials, and demonstrated superior activity for both the OER and HER and outstanding stability over the amorphous and crystalline counterparts. Notably, the SemiAmp||SemiAmp electrolyzer demonstrated a better performance for overall water splitting than the commercial RuO2||Pt/C electrolyzer.
Keywords: amorphous; CoWO4; electrocatalyst; HER; Nanocomposite; OER; water splitting